Síntese e Caracterização de Polímeros Molecularmente Impressos para Determinação de Cocaína em Urina empregando a Microextração em Sorvente Empacotado - Ferreira, Juliana Barreto (2021)
For decades, the number of users of drugs of abuse has increased considerably. The use of these substances, as they cause chemical dependence, generates problems that not only affect the user himself, but also the people who live around them, becoming one of the main public health problems in the world. The present work presents the synthesis and characterization of Molecularly Imprinted Polymers (MIPs) for application in the preparation of biological samples using a home-made device for Microextraction in Packed Sorbent (MEPS) of cocaine. The MIPs synthesized from caffeine as a template molecule were compared with MIPS produced using cocaine itself as a template. That's because caffeine is a cheaper and easier to obtain than cocaine. In addition, Restricted Access Molecularly Imprinted Polymers (RAMIPs) were also produced for comparison purposes. The polymeric materials were characterized by the techniques of Scanning Electron Microscopy (SEM), textural analysis, Fourier Transform Infrared Spectroscopy (FT-IR) and Cross Polarization/Magic Angle Spinning 13C Nuclear Magnetic Resonance (CP/MAS 13C NMR). The method optimization was performed by LTQMS evaluating the effects of sample pH and elution solvent, washing solvent, adsorption cycles and eluent volume. In the characterization, the results showed that the non-coated polymers have a large specific surface area in the range of 230 to 463 m2 g -1 and similar carbon structure. In the optimized method, RAMIPs indicated better cocaine extraction compared to MIPs. The quantitative study demonstrated that the developed method was able to quantify cocaine in urine samples with values close to actual concentrations.